NUMERICAL STUDY THE EFFECT OF AIR BARRIERS HEIGHT INSIDE THE AIR CONDITIONING DUCTING TO SATISFY THE REGULATION OF INDONESIA MINISTER OF TRANSPORTATION NUMBER 69 OF 2019 - Fauzun, Fauzun; Yogiswara, Cahyo Wibi; Ariyadi, Hifni Mukhtar; Taufiqurrahman, Muhammad Salim; Ritonga, Aldy Franstanata; Pranoto, Indro; Garingging, Rendianto Aginta; Areli, Fakhreza; Putra, Rahma Kurnia; Al-Qadri, Maulana Hafizh; Fatkhi, Afrizal Soffan; Nurdiansyah, Rahardian Titus; et al. (Journal of Applied Engineering Science, 2023)
The Indonesian smart hybrid light train is a train under development by the government and will operate in Makassar-Parepare, Indonesia track. The authors conducted a numerical study on CFD to investigate the air flow distribution inside the air conditioning ducting and the air velocity and air temperature distribution on Motor Engine and Compartment (MEC) car to achieve the passenger comfort criteria based on the regulation standard of Indonesia Minister of Transportation Number 69 of 2019. This study was conducted by simulating 5 variations of air barriers height inside the supply ducts. The input of air into the ducting has the parameters of mass flow rate, static temperature, static pressure, and density with the values of 1 kg/s, 20 °C, 1 atm, and 1.2 kg/m3, respectively. The simulation results show that variation E is the best design which generated the average air velocity and air temperature distribution in the executive passenger cabin with the values of 0.25 m/s and 21.91 °C, respectively. Meanwhile, the other 4 variations did not satisfy the standard. The results also show that the ducting geometry can accommodate the air temperature difference on the MEC car that does not exceed 1.5 °C and the air supply is sufficient from the air conditioner unit to the driver room.